The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/erv.2667
|View full text |Cite
|
Sign up to set email alerts
|

Clinical management of females seeking fertility treatment and of pregnant females with eating disorders

Abstract: The presence of eating disorders (EDs) might have a significant impact upon pregnancy, birth, and the offspring's well‐being. Thus, several specific aspects are to be considered by medical professionals when females with EDs either become pregnant or intend to undergo fertility treatment. Clinical management algorithms for gynaecologists and fertility specialists are missing. Here, based on currently available evidence on the topic, specific clinical recommendations are presented. Treatment by a mental health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 55 publications
0
10
0
4
Order By: Relevance
“…For example, fetal magnetoencephalography (fMEG) is a non-invasive method to study fetal brain activity, which has previously revealed evidence that the maternal metabolism might program the fetal brain [60,61]. However, the first step is the adequate assessment and identification of EDs through medical professionals (general practitioner, gynecologist, or fertility specialist), ideally before pregnancy [62]. Paslakis and de Zwaan [62] recently provided clinical recommendations and specific algorithms for the management of pregnant females with EDs and for females with EDs seeking fertility treatment, underlining the importance of an interdisciplinary approach.…”
Section: Discussionmentioning
confidence: 99%
“…For example, fetal magnetoencephalography (fMEG) is a non-invasive method to study fetal brain activity, which has previously revealed evidence that the maternal metabolism might program the fetal brain [60,61]. However, the first step is the adequate assessment and identification of EDs through medical professionals (general practitioner, gynecologist, or fertility specialist), ideally before pregnancy [62]. Paslakis and de Zwaan [62] recently provided clinical recommendations and specific algorithms for the management of pregnant females with EDs and for females with EDs seeking fertility treatment, underlining the importance of an interdisciplinary approach.…”
Section: Discussionmentioning
confidence: 99%
“…The best approach for pregnant women with EDs implies a multidisciplinary management comprised of gynecologists, midwives, nutritionists, and mental health professionals working as a team. However, there is an insufficient medical training to openly discuss eating behaviors with the patient (29). Women with EDs do not often disclose this information to clinicians due to fear of stigmatization or misunderstanding.…”
Section: Eds During Pregnancy: Target Therapymentioning
confidence: 99%
“…Recent evidence showed that maternal disordered eating behaviors impact the course of pregnancy and fetal development. Updated reviews of the literature highlighted that the major obstetric and gynecologic complications were infertility, high rate of miscarriage, poor nutrition during pregnancy, hyperemesis gravidarum, cesarean section, preterm delivery, and postpartum depression (27)(28)(29)(30). The most described detrimental effects on fetal development were fetal growth delay, small for gestational age babies and small head circumference, low Apgar score and an increased risk of perinatal mortality (27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…The findings highlight the importance of consistency in the diagnostic criteria operationalised in studies and support the validation of suitable instruments for use with antenatal populations (Bannatyne, Hughes, Stapleton, Watt, & MacKenzie‐Shalders, ). In a recent article by Paslakis and de Zwaan (Paslakis & Zwaan, ), the lack of appropriate algorithms for identifying ED in pregnant women was highlighted.…”
Section: Discussionmentioning
confidence: 99%